Organization Planning: Whose Responsibility? - Bailey, Joseph (Academy of Management Journal, 1964)
The article presents information on a study which examined the different approaches in organizational planning of corporations in the U.S. Evidence of the variety of approaches used by the 639 companies cooperating in the preliminary phases of the study is discussed. As the analysis of preliminary responses proceeded, it was hypothesized that a large majority of the companies resolved organization planning responsibilities in one of six categories. A discussion is presented about methods used by corporations to effectively plan for the development of the organization.